(untitled) (Pedagogy of Higher and Secondary Education, 2012)
Palazhenko O. Pedagogical recommendations for adaptation to the conditions of the respiratory system play a wind instrument. In the article it is systematized and methodically grounded basic pedagogical recommendations in relation to adaptation of the respiratory system to the terms of game on wind instruments.